Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1445-2197.1989.tb07013.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Msa Levels in Normal Women and Women With Breast Cancer

Abstract: Blood from 1497 women who were either non‐pregnant, pregnant at all stages of gestation, lactating after parturition, postmenopausal, or who had benign breast lumps, primary breast cancer or advanced breast cancer were tested for their peripheral blood mammary serum antigen (MSA), using the 3E1.2 monoclonal antibody (MoAb) in an inhibition enzyme linked immunosorbent assay test system. The study aimed to establish normal ranges for comparison with MSA levels in breast cancer and benign breast disease. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This represents a significantly smaller percentage of advanced breast cancer patients who have raised circulating MSA levels compared to the published data [3]. We have discussed this discrepancy in a previous report, which concluded that measurement of serum MSA levels would be of no use in the detection of early (Stage I and Stage II) breast cancer [6]. In that report we suggested that serial measurements of serum MSA might be useful in the management of advanced breast cancer, and this paper reports the results of a study to explore this possibility.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…This represents a significantly smaller percentage of advanced breast cancer patients who have raised circulating MSA levels compared to the published data [3]. We have discussed this discrepancy in a previous report, which concluded that measurement of serum MSA levels would be of no use in the detection of early (Stage I and Stage II) breast cancer [6]. In that report we suggested that serial measurements of serum MSA might be useful in the management of advanced breast cancer, and this paper reports the results of a study to explore this possibility.…”
Section: Discussionmentioning
confidence: 45%
“…A modification of the Stacker ELISA assay [8] was used as previously described [6]. In our laboratory an arbitrary value of > 400 inhibition unit/ml (IU/ ml) is taken to indicate the presence of an abnormal MSA level in the serum.…”
Section: Msa Detection Assaymentioning
confidence: 99%
See 2 more Smart Citations